DAMMARANE-TYPE TRITERPENOIDS FROM THE STEMBARK OF CHISOCHETON PENTANDRUS (MELIACEAE) - Katja, D. G.; Salam, S.; Nurlelasari, .; Harneti, D.; Maharani, R.; Supratman, U.; Shiono, Y. (Jurnal Kimia (Journal of Chemistry), 2020)
Two dammarane-type triterpenoids, cabraleadiol ( 1 ) and cabraleahydroxylactone ( 2 ), have been isolated from n -hexane extract of the stembark of   Chisocheton pentandrus (Meliaceae). The structure of compounds 1 and 2 were determined by spectroscopic data mainly NMR and mass as well as by comparing with previously reported spectral data. Compounds 1 and 2 were reported for the first time from Chisocheton pentandrus .   Keywords:   Cabraleadiol, Cabraleahydroxylactone, Chisocheton pentandrus , Meliaceae.